Protected Code Stroke: Hyperacute Stroke Management During the Coronavirus Disease 2019 (COVID-19) Pandemic. Issue 6 (June 2020) - Khosravani, Houman; Rajendram, Phavalan; Notario, Lowyl; Chapman, Martin G.; Menon, Bijoy K.
Abstract : Background and Purpose—: Hyperacute assessment and management of patients with stroke, termed code stroke, is a time-sensitive and high-stakes clinical scenario. In the context of the current coronavirus disease 2019 (COVID-19) pandemic caused by the SARS-CoV-2 virus, the ability to deliver timely and efficacious care must be balanced with the risk of infectious exposure to the clinical team. Furthermore, rapid and effective stroke care remains paramount to achieve maximal functional recovery for those needing admission and to triage care appropriately for those who may be presenting with neurological symptoms but have an alternative diagnosis. Methods—: Available resources, COVID-19-specific infection prevention and control recommendations, and expert consensus were used to identify clinical screening criteria for patients and provide the required nuanced considerations for the healthcare team, thereby modifying the conventional code stroke processes to achieve a protected designation. Results—: A protected code stroke algorithm was developed. Features specific to prenotification and clinical status of the patient were used to define precode screening. These include primary infectious symptoms, clinical, and examination features. A focused framework was then developed with regard to a protected code stroke. We outline the specifics of personal protective equipment use and considerations thereof including aspects of crisis resource management impacting team role designation and human performance factors during a protected code stroke. Conclusions—: We introduce the concept of a protected code stroke during a pandemic, as in the case of COVID-19, and provide a framework for key considerations including screening, personal protective equipment, and crisis resource management. These considerations and suggested algorithms can be utilized and adapted for local practice.